Hypoxemia found after hospitalization with right hemiplegia due to cerebral infarction: platypnea-orthodeoxia syndrome in the older people. Issue 2 (February 2022) - Tachibana, Masatoshi; Kanemaru, Akiko; Hatano, Keiko; Murata, Teppei; Ishikawa, Joji; Harada, Kazumasa
Abstract: An 89-year-old woman was admitted to our hospital for subacute onset of right upper and lower limb weakness and was diagnosed with acute cerebral infarction. During rehabilitation, close observation revealed that her oxygen saturation decreased in the sitting position and improved in the recumbent position without any subjective symptoms of dyspnea. Transthoracic and transesophageal echocardiography and cardiac catheterization revealed a large patent foramen ovale with an atrial septal aneurysm with right-to-left shunting through the defect, and she was diagnosed with platypnea-orthodeoxia syndrome. Her right hemiplegia caused the trunk to collapse, so the patient slumped when in sitting position, and the trunk tilted to the right forward, resulting in an increased right-to-left shunt. Her peripheral capillary oxygen saturation improved in the upright sitting position supported by therapists. This case suggests that right hemiplegia may exacerbate the symptoms of platypnea-orthodeoxia syndrome. <Learning objective: Platypnea-orthodoxia syndrome (POS) is a rare disease and often not clearly diagnosed. Previous studies have reported POS due to patent foramen ovale (PFO) after the onset of subclinical cerebral infarction. To our knowledge, this is the first case to suggest that trunk collapse during sitting due to right hemiplegia exacerbated the hypoxemia caused by POS. Moreover, 20–30% of adults may have asymptomatic PFO. POS may be detected by examining changes in oxygen saturation in different postures.>